Characteristics of scientific production in Croatia from 1997 to 2014 - Pečarić, Đilda; Baković, Božidar; Tuđman, Miroslav (Qualitative and Quantitative Methods in Libraries, 2017)
Common practice today is to evaluate scientific production and influence of scientists through the Journal Impact Factor and citations of scientific papers. In this way, the Science Citation Index (SCI) and Current Contents (CC) have also become the main criterion for evaluating national scientific production. The consequence of this approach is that we have no insight into the overall scientific production in certain countries or certain scientific fields. The aim of this work was to give review of the overall scientific production in Croatia. Analysis of productions of Croatian scientists was done on the corpus to 413,855 bibliographic units registered in the Croatian scientific bibliography database (CROSBI) in the period from 1997 to 2014. The Croatian scientific bibliography database (CROSBI) provides the most comprehensive presentation of scientific production in Croatia, and analyzes the productivity of the scientific community, by scientific fields and duration of research projects. Also, with an analysis of the dominant types of scientific papers in various scientific fields (book, journal, book chapter, proceedings, etc.). In contrast to the evaluation of science and scientists by citation database and Impact Factor, complete analysis of scientific production provides a presentation of the whole scientific activity and responsibilities of scientists and university academics, whose task is to be mentors to doctoral candidates and young researchers who are typically involved in research projects, as well as writing textbooks, reviews etc. The understanding of the scientific production of any scientific community requires new methods for evaluation of scientific efficiency. Most commonly used as an indicator, Impact Factor allows only fragmentary approach and usually only evaluation of the international impact of certain scientists and journals.